Recommendations for the management of septic arthritis after ACL reconstruction - Wang, Cheng; Lee, Yee Han Dave; Siebold, Rainer (Knee surgery, sports traumatology, arthroscopy, 2014)
To evaluate the current evidence for the management of septic arthritis after anterior cruciate ligament (ACL) reconstruction, the factors that affect the outcome after treatment and the retention of graft and implants.
Published online: 6 September 2013
Gesehen am 18.09.2020